EFFECT OF BREEDING AND NON BREEDING SEASONS ON POST THAW QUALITY OF STALLION SEMEN - KUMAR, DEVENDER; JHAMB, DINESH; KUMAR, NAVEEN; SAXENA, ATUL (The Indian Journal of Animal Reproduction, 2023)
Present study was aimed to compare the different cryoprotective agents for semen of Indian stallionsduring the breeding season (BS) and non breeding season (NBS). Basic extender used was INRA 82 addedwith 2 per cent egg yolk. The freezing extenders contained the basic extender added with any of the threedifferent cryoprotectants viz dimethyl formamide (DMF), glycerol (GLY) and ethylene glycol (EG) added singlyor in combination. The freezing extender E1 contained 2% DMF, E2 contained 2% GLY, E3 contained 2% EGand extender E4 contained 1 % DMF + 1 % GL Y. Semen was thawed at 60°C for 8 sec and post thaw per centmotility (M), viability (V) and positive sperms to HOST (H) was assessed.The minimum M was found in E1 (26.51 ± 01.20 %) and E2 (36.38 ± 2.07 %) in BS and NBS respectively,while maximum M was found in E4 (28.74 ± 1.39 %) and E1 (39.12 ± 02.08 %). The minimum V was found inE1 (22.63 ± 01.19 %) and E3 (29.72 ± 01.52 %) in BS and NBS respectively, while maximum was observed inE4 (26.52 ±1.23%), and E2 (32.83 ± 01.67 %). Minimum H was found in E2 (28.60 ± 01.36 %) and (46.00 ±02.11 % ) in BS and NBS respectively, however, maximum H was found in semen cryopreserved in E4 (32.63 ±01.01 %) and (49.03 ± 01.96 %). Overall extender E4 proved best for cryopreserving stallion semen in Indianconditions followed by E1. While comparing the seasons, the overall values for M, V & H were significantlyhigher in NBS as compared to BS.
Keywords: Stallion semen; Cryopreservation; Cryoprotectants and Seminal attributes; Breeding season